2022
DOI: 10.3389/fnana.2022.1012422
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of naringin against cerebellar changes in Alzheimer’s disease through modulation of autophagy, oxidative stress and tau expression: An experimental study

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by gradual cognitive decline. Strong antioxidants that inhibit free radicals, such as polyphenols, reduce the likelihood of developing oxidative stress-related degenerative diseases such as AD. Naringin, a flavonoid found in citrus fruit shown to be neuroprotective, reduce oxidative damage and minimize histopathological changes caused by ischemic reperfusion, enhance the long-term memory in AD animal models. This work aimed to comprehend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…GCs with extensive vacuolations, an irregular nuclear membrane, a dilated Golgi complex and a marked decrease in granule cell precursors are observed in tramadol-treated groups. The observed morphological alterations in the GCL as a result of tramadol treatment in the present study are consistent with previous research indicating that cerebellar granule neurons are particularly susceptible to oxidative stress-related conditions (Kaur et al 2007 ; Hassan et al 2022 ). Cerebellar granule cell neurons are characterized by their high energy demand and comparatively low ATP levels, in addition to their heightened transcriptional activity of genes linked to oxidative stress and inflammatory responses (Wang et al 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…GCs with extensive vacuolations, an irregular nuclear membrane, a dilated Golgi complex and a marked decrease in granule cell precursors are observed in tramadol-treated groups. The observed morphological alterations in the GCL as a result of tramadol treatment in the present study are consistent with previous research indicating that cerebellar granule neurons are particularly susceptible to oxidative stress-related conditions (Kaur et al 2007 ; Hassan et al 2022 ). Cerebellar granule cell neurons are characterized by their high energy demand and comparatively low ATP levels, in addition to their heightened transcriptional activity of genes linked to oxidative stress and inflammatory responses (Wang et al 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…A number of flavonoids have also been shown to have neuroprotective and neuroregenerative properties. Preclinical studies in rodent, pig, and monkey models of AD, PD, HD, and ALS [ 34 , 249 , 250 , 251 , 252 , 253 , 254 , 255 ] have also demonstrated that flavonoids have properties that counter neuroinflammation, prevent the neurotoxic effects of pathological protein aggregates of amyloid and hyperphosphorylated tau protein, free radical generation from peroxidation of lipids, and that brain tissues are rich in phospholipids that are susceptible to oxygen radical release during neuroinflammation. Some flavonoids act as monoamine oxidase inhibitors, combat apoptosis, are neuroprotective, promote neurogenesis and memory, and reduce cognitive decline [ 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ].…”
Section: The Potential Of Flavonoids In Tissue Repair Processes In a ...mentioning
confidence: 99%
“…Three different colored images were created using a color deconvolution plug-in and the H-DAB-vector as the selected color: green, brown, and blue. The DAB images (brown in color) were calibrated using area fraction ( Hassan et al, 2022 ). The threshold was adjusted for more precision.…”
Section: Methodsmentioning
confidence: 99%